"Free" Not to Engage: Neoliberal Ideology and Collective Action. The Case of the Yellow Vest Movement. Issue 1 (5th May 2020) - Girerd, Lola; Anne Ray, Frédérique; Priolo, Daniel; Codou, Olivier; Bonnot, Virginie
The purpose of this paper is to test the main hypothesis that the endorsement of neoliberal ideology, comprising beliefs and values such as personal responsibility and hedonism, is negatively associated with the engagement in the Yellow Vest (YV) movement. In a first study (N = 489), analysis of qualitative data shows that most of the YV movement grievances are system challenging. Furthermore, consistent with our hypotheses, the more participants endorsed neoliberal ideology, the less they perceived inequalities against the lower and middle classes, the less angry they felt in the face of such inequalities, the less they identified with the Yellow Vests and finally, the less they engaged in the Yellow Vest movement. In Study 2 (N = 201), the relationship between neoliberal ideology, measured in a different way, and engagement in the movement was replicated amongst a sample of participants who support the YV movement. Moreover, it appeared that this relationship was mediated by a greater sense of personal control, leading to a higher level of system justification. In fact, neoliberal ideology appears to enhance personal control, giving them a heightened sense that the system is just and legitimate. This perception, in turn, appears to undermine the politicized identification with the Yellow Vest and as a consequence, engagement in the movement.